Effects of vitamin D receptor gene polymorphisms on the prognosis of COVID-19 - TİGEN, ELİF; HAKLAR, GONCAGÜL; ATA, PINAR (My University, 2021)
PURPOSE: Vitamin D deficiency has emerged as another potential risk factor for coronavirus disease (COVID-19) due to the immunomodulatory effects of 25 hydroxyvitamin D [25 (OH)D]. Vitamin D receptor (VDR) gene polymorphisms such as Fok I, Bsm I, Apa I, and Taq I are also associated with different courses of viral infections. This study aimed to evaluate the association between the VDR gene polymorphism at Fok I, Taq I, Bsm I, and Apa I genotypes and the prognosis of COVID-19 in respect to vitamin D deficiency. METHODS: Two-hundred ninety-seven patients with COVID-19 were enrolled. Serum 25 (OH)D levels were measured. Four variant regions of the VDR gene, FokI, BsmI, ApaI, and TaqI were determined. RESULTS: Eighty-three percent of subjects had vitamin D deficiency, and 40.7% of the whole group had severe deficiency. Median 25 (OH)D level was 11.97 ng/ml. Vitamin D levels were not related to inflammatory markers, disease severity, admission to intensive care unit (ICU), and mortality. While disease severity was related to Fok I Ff genotype, it was Taq TT genotype for ICU admission. Moreover, the ApaI aa genotype was common among the patients who were died. None of the deceased subjects had the Fok I FF genotype. CONCLUSION: 25 (OH)D levels were not related to the severity and mortality of COVID-19. VDR gene polymorphisms are independently associated with the severity of COVID-19 and the survival of patients.
Keywords: COVID-19; vitamin D deficiency; Apa I; Fok I; VDR polymorphism